استشراقی انگريزی قرآنی تراجم ميں وحی اور متن قرآن پر تنقيدات کا تجزياتی مطالعہ - Farhat Naseem; Afshan Noureen (البصيرة, 2023)
The orientalist movement has played a pivotal role in raising criticism against revelation, Surah arrangement, writing style (orthography) and pronunciation (recitation) of Holy Quran. The Oriental scholars who mostly belonged to radical/religious Jew-Christian back ground, theorized that basic source of creation of Quran was Torah and Biblical verses. These oriental scholars also insisted in their writings that Quran went under multiple evolutionary changes and many changes took place in this Holy book to be in the shape in which it exists today. The orientalist scholars’ accusations on Holy Prophet Muhammad (P.B.U.H) regarding divinastion, Hallucination and self-creation of Ayah/Surahs are also an important part of oriental literature. This study provides brief but comprehensive overview of above mentioned oriental scholars literary conspiracy and criticism on Quran text and also challenges them with logical response to prove that Quran is a word of God revealed upon the last Prophet Muhammad (P.B.U.H).